Pelatihan Penulisan Feature Pengalaman Warga Selama Masa Pandemi di Desa Tamantirto, Kasihan, Bantul - Pujiharto, Pujiharto; Soleh, Rakhmat; Anwar, Saeful (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
Tamantirto village, Kasihan, Bantul is an area which is positively responsive in terms of dealing with the Covid-19 pandemic. The citizens’ response is not only showed by implementing health protocol and entrances shutdown during the pandemic, but is also empowered by the consciousness of knowledge and experience transfer about pandemic for the next generation. Through the existing village’s information system, they offer a collaboration to lecturer of Indonesian Language and Letter Study Program of FIB UGM in order to conduct feature writing training about citizens’ point of view and experience during the pandemic. The training is held in two methods. The first is direct training method with power point elaborating the definition, type, example, and writing technique and feature editing. The second one is writing guidance using WA group where the participants can send their work to the group chat and then the trainer give feedback for the document. The training produce 21 feature documents which are averagely elaborate the participants’ profession regarding with the pandemic. Most of the documents are written with argumentative paragraph instead of narrating their experience during the pandemic like the common feature which is tend to be narrative. ===== Desa Tamantirto, Kasihan, Bantul merupakan wilayah yang tanggap dalam menghadapi pandemi Covid-19. Ketanggapan warga tidak hanya ditunjukkan melalui penerapan protokal kesehatan dan penutupan sejumlah pintu gang ketika masa pandemi, tetapi juga didukung pada kesadaran akan pentingnya pewarisan pengetahuan dan pengalaman seputar pandemi kepada generasi mendatang. Melalui Tim Sistem Informasi Desa yang mereka miliki, mereka mengajak kerja sama dengan dosen Prodi Bahasa dan Sastra Indonesia FIB UGM untuk mengadakan kegiatan pelatihan penulisan feature seputar pandangan dan pengalaman warga selama pandemi. Pelatihan diselenggarakan dengan dua cara. Pertama, pelatihan secara langsung dengan media power point yang menguraikan definisi, jenis, contoh, dan teknik penulisan serta penyuntingan feature. Kedua, bimbingan penulisan melalui WA Grup ketika peserta mengirimkan karyanya ke grup WA dan narasumber memberikan masukan terhadap naskah tersebut. Pelatihan menghasilkan 21 naskah feature yang rata-rata menguraikan profesi para peserta dan mengaitkannya dengan pandemi. Sebagian besar naskah masih lebih banyak diisi dengan paragrat argumentatif dibandingkan menarasikan pengalaman selama pandemi sebagaimana layaknya feature yang cenderung naratif.